2016
DOI: 10.21123/bsj.2016.13.2.2ncc.0447
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Water-Soluble Vitamins in Iraqi Honey Bee and Compare with Others Types by High –Performance Liquid Chromatography

Abstract: A histological study showed the wall of the stomach in Pica pica and Herpestes javanicus consists of four layers: mucosa, submucosa, muscularis externa and serosa. Also, the present study showed many differences in the histological structures of the stomach for each in both types. The stomach of P. pica consists of two portions: the proventiculus and gizzard, while the stomach of H. javanicus consists of three portions: cardiac, fundic and pyloric regions. The mucosa layer formed short gastric folds, named pli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…2 compounds like alcohols, phenols, ketones, organic acids, and esters with antibacterial, antifungal, and anticancer activity. Hamed et al [8] focused to determination of water-soluble vitamins of Bcomplex group in Iraqi honeys by HPLC method. Al-Hasani et al [9] detected antibacterial effect of Iraqi honey samples against gram-positive and gram-negative bacteria at concentration of 100 % and the inhibition effect of honey decreased as honey diluted.…”
Section: Introductionmentioning
confidence: 99%
“…2 compounds like alcohols, phenols, ketones, organic acids, and esters with antibacterial, antifungal, and anticancer activity. Hamed et al [8] focused to determination of water-soluble vitamins of Bcomplex group in Iraqi honeys by HPLC method. Al-Hasani et al [9] detected antibacterial effect of Iraqi honey samples against gram-positive and gram-negative bacteria at concentration of 100 % and the inhibition effect of honey decreased as honey diluted.…”
Section: Introductionmentioning
confidence: 99%
“…The second type is called the "Siyafi" or "Al-Ghashima" (Wild) bee strain, whose workers are dark in color and aggressive in nature [7]. [8] studied the most important water-soluble vitamins in the local Iraqi honey bee strain and compared them with imported bee strains, finding many differences that may be considered as future classification characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have found that the honeybees found in the central regions of Iraq differ in morphological measurements from the Carniolan and IOP Publishing doi:10.1088/1755-1315/1262/3/032028 2 Italian honeybees, it is suggested that they are closer to the subspecies of Syrian honeybee, Apis mellifera syriaca [3]. The important water-soluble vitamins were studied in the local Iraqi honeybee strain and compared to imported honeybee strains, revealing several differences that could be considered as potential future classification traits [4]. Honeybee colonies can be affected by various diseases and pests, including American Foulbrood (AFB), European Foulbrood (EFB), infestation by Varroa mites (Varroa), Nosema infection (Nosema), and others [5,6].…”
Section: Introductionmentioning
confidence: 99%